Conditional cash transfers and social welfare. A look into two Latin American case studies (Comillas Journal of International Relations, 2015)
This paper analyses the role of conditional cash transfers (CCT) in improving social indicators during the past decade in Brazil and Peru. Barely two decades after the appearance of the first programmes, CCTs – cash transfers to families living in poverty or extreme poverty conditioned to school attendance and compulsory medical visits for children – are now one of the main policy tools in the fight against poverty in dozens of developing countries. More specifically, this paper examines the link between the CCT programme in each of these two countries – the giant Bolsa Familia in Brazil, the pioneer and largest program of this type in the world, and Juntos in Peru, smaller in terms of size and relevance, but practically identical in its design – and the evolution of social indicators relative to poverty, education and health.
Keywords: conditional cash transfers (CCT); social development; Brazil; Peru; Bolsa Familia; Juntos